Bibliometric analysis: most discussed topics ethnochemistry in chemistry learning - Utami, Resty; Astutik, Trining Puji (Eclética Química, 2025)
Ethnochemistry, integrating local culture with chemistry education, enhances students’ comprehension by relating lessons to everyday life. This study utilizes bibliometric analysis to identify prevalent topics in ethnochemistry research within chemistry learning from February 2018 to January 2023. Using Publish or Perish (PoP) software, Google Scholar, and the VOSviewer application, 31 journal articles were analyzed to reveal key themes and trends. The findings indicate a strong association of ethnochemistry with terms like “guidelines,” “development,” “implementation,” “local wisdom,” “ability achieved,” and “learning process”. Ethnochemistry has shown significant potential to make chemistry learning more engaging and relevant by linking abstract concepts to cultural and everyday contexts. However, the integration of ethnochemistry into curricula is still limited, and practical applications in modern education remain underexplored. This study highlights the importance of developing strategies to incorporate ethnochemistry into teaching and research, fostering critical thinking, scientific literacy, and cultural appreciation among students. The findings offer a framework for future studies, encouraging innovative approaches that bridge science education with cultural heritage to create more meaningful learning experiences.